Effects of molybdenum nanoparticles on the interface between lead-free solder and nickel substrate / Mohammad Hossein Mahdavifard - Mohammad Hossein, Mahdavifard (2013)
In this study, Mo nanoparticles were used as a reinforcing material into the Sn-3.8Ag- 0.7Cu (SAC) solder on the nickel substrate (Cu substrate with an electrodeposited Ni layer on top). The Mo nanoparticles were characterized by transmission electron microscopy (TEM) and X-ray diffractometer (XRD). The composite solder paste was prepared by manually mixing Mo nanoparticles with the SAC solder paste. Nickel was electrodeposited on polycrystalline copper substrate in the Watts bath. The solder paste was placed on substrate at 250ºC for 45 seconds. After reflow, elemental compositions of the nanocomposite solders were analyzed by inductively coupled plasma-optical emission spectrometer (ICP-OES). The microstructural investigations, spreading rate and wetting angle measurement were carried out on the solders after first reflow. After that one set of samples were subjected to multiple reflow for up to six times. Microstructural investigations were performed at the solder/substrate interface using high resolution field emission scanning electron microscopy (FESEM) and energy dispersive X-ray (EDX). Results reveal that after reflow only a fraction of Mo nanoparticles were retained inside the solder matrix. The solder spreading rate was decreased and wetting angle increased with the addition of Mo nanoparticles to the SAC solder. It was found that Mo nanoparticles were effective in suppressing the growth of total IMC layer thickness and scallop diameter during reflow. It was found that Mo nanoparticles did not dissolve or react with the solder during reflow. The retardation of IMC thickness was suggested to be due to the discrete particle effect of Mo nanoparticles. The intact, discrete nanoparticles, by absorbing preferentially at the interface, hindered the diffusion flux of the substrate and thereby suppressed the IMC growth. The retardation of total IMC layer with the addition of Mo nanoparticles is expected to improve the reliability of the solder joint.